Perspectives on the knowledge-based society: An introduction to the special issue - Katharine Rockett (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
Knowledge exchange, innovation policy, and international trade flows are key aspects of the knowledge-based economy. In her introduction to the special issue on The Knowledge-Based Society: Transition, Geography, and Competition Policy the author briefly reviews these aspects. She begins with spillovers, emphasising the effects that drive the variety of results in this literature, and their role in a model of research joint venture formation among asymmetric partners. She then moves on to the linkages between universities and industry, underlining the diversity of these linkages and their goals. She discusses the interaction among innovative skills, minimum quality standards, and patent protection, noting how these generate welfare outcomes that vary with industry innovative skill levels. Finally, the author examines threshold effects in the relation between innovation and exports.
Keywords: F12; L1; L2; L5; O3; R12; 330; exports; innovation; intellectual property; quality standards; research joint ventures; spillovers; university impact